Gender discrimination and the acquisition of competitive advantage: A neoliberal history of profitable exploitation - Chidiac, Christelle (Kent Law Review, 2017)
Globalisation has been essentially based on free trade theory and comparative advantage which promote liberalization, privatization and deregulation to supposedly achieve gains for every country and its citizens. The World Trade Organisation has played a central role in legitimizing this theory. However, it does so in a gender-blind manner, which has been criticized essentially in the feminist literature for missing out on the ways in which the acquisition of competitive advantage is a gendered process and how gender inequality serves as a tool for such acquisition. This paper will address this problem first, by examining the practical consequences of the WTO agreements in using women as source of competitive advantage in some instances but also in excluding them from trade openness in others. Further, the issue of the unpaid care economy and social reproduction and its inherent gender impact shall be addressed. It will analyze the ways in which some women may benefit from trade liberalization while others will be left worse off. This paper concludes by questioning the accuracy of the theory of comparative advantage and the concept of development. It highlights the crucial role of feminist contributions to challenging the neoliberal discourse.